Market reactions to voluntary disclosures of a strategic alliance agreement: evidence from China. Issue 2 (3rd April 2023) - Zhang, Xinyue; Li, Wanli; Gao, Simon
ABSTRACT: This paper examines the market reaction to strategic alliance agreements (SAAs), a prevalent yet previously uninvestigated corporate voluntary disclosure practice. We document that investors react positively to SAA disclosures in short windows, and that the effect of SAA disclosures is transitory, since a reversal occurs within 30 days after the disclosure. We also find that the market reaction is weaker to an SAA involving the progress of existing cooperation projects and that markets react more positively to SAAs disclosed by firms that had released progress reports before. The results of cross-sectional tests indicate that investor sophistication and being a high-technology firm strengthen the association between SAA characteristics and market reactions. Finally, we document that market reaction decreased after the passage of the SAA format guidelines in 2015 and after firms have received a comment letter related to an SAA. Overall, our findings indicate that SAA disclosure is a crucial information resource for investors.